SARS-CoV-2 pan-variant inhibitory peptides deter S1-ACE2 interaction and neutralize delta and omicron pseudoviruses - Shah, Masaud; Ung Moon, Sung; Hyun Kim, Jang; Thanh Thao, Trinh; Goo Woo, Hyun (Computational and Structural Biotechnology Journal, 2022)
Approved neutralizing antibodies that target the prototype Spike are losing their potency against the emerging variants of concern (VOCs) of SARS-CoV-2, particularly Omicron. Although SARS-CoV-2 is continuously adapting the host environment, emerging variants recognize the same ACE2 receptor for cell entry. Protein and peptide decoys derived from ACE2 or Spike proteins may hold the pan-variant inhibitory potential. Here, we deployed interactive structure- and pharmacophore-based approaches to design short and stable peptides –Coronavirus Spike Neutralizing Peptides (CSNPs)– capable of neutralizing all SARS-CoV-2 VOCs. After in silico structural stability investigation and free energies perturbation of the isolated and target-bound peptides, nine candidate peptides were evaluated for the biophysical interaction through SPR assay. CSNP1, CSNP2, and Pep1 dose-dependently bind the S1 domain of the prototype Spike, whereas CSNP4 binds both S1 and ACE2. After safety and immunocytochemistry evaluation, peptides were probed for their pan-variant inhibitory effects. CSNP1, CSNP2, and CSNP4 inhibited all VOCs dose-dependently, whereas Pep1 had a moderate effect. CSNP2 and CSNP4 could neutralize the wild-type pseudovirus up to 80 % when treated at 0.5 µM. Furthermore, CSNP4 synergize the neutralization effect of monoclonal antibody and CSNP1 in Delta variant pseudovirus assay as they target different regions on the RBD. Thus, we suggest that CSNPs are SARS-CoV-2 pan-variant inhibitory candidates for COVID-19 therapy, which may pave the way for combating the emerging immune-escaping variants. We also propose that CSNP1/2-CSNP4 peptide cocktail or CSNP1/4 mAbs cocktail with no overlapping epitopes could be effective therapeutic strategies against COVID-19.
Keywords: ACE2; Coronaviruses; Inhibitory peptides; Neutralisation; Neutralizing antibodies; Omicron; Peptide-cocktail; Spike; Spike protein; Variant of concern; ACE2; Neutralization; Omicron; Peptides-Cocktail; SARS-CoV-2; Spike; VOCs